Investigation of odor emissions from coating products: Key factors and key odorants - Pei, Yipu; Liu, Ning; Liu, Shihua; Guan, Hongyan; Guo, Zhongbao; Li, Qiannan; Han, Wei; Cai, Hanmei (Frontiers in Environmental Science, 2022)
Coating products are widely used for the interior decoration of residential property. However, there is growing concern regarding their odor emissions and their impact on indoor air quality (IAQ). Most manufacturers and government agencies set odor intensity limits to control the odor of coating products, including their raw materials. However, it is difficult to determine product performance by means of their odor intensity index. Although evaluating odor intensity requires odor evaluators to distinguish between different intensity levels, low consensus and reproducibility represent challenges that are difficult to avoid. As the odor concentration index only requires odor assessors to ascertain whether the odor is felt or not, the reproducibility of the evaluation results is relatively better. Moreover, suitable methodologies for determining odor concentrations in volatile coating product emissions have rarely been reported. Therefore, establishing an evaluation method for odor concentration of coating products and exploring its key influencing factors should bridge this gap. We examined the influence of the airbag material on the recovery rate of typical volatile organic compounds (VOCs) using direct injection by GC-MS and established that their adsorption effects were in the order: PET > PVF > PTFE. We then explored the influences of the sample curing and odor emission times on odor concentration. The solvent-based and water-based coatings reached equilibrium after 8 h and 16 h curing, respectively, and after 8 h and 12 h odor emission, respectively. The odor concentrations of real coating samples were measured and compared against their odor intensities. The odor concentration method more accurately and reliably discriminated coating products than the odor intensity approach. Thus, to assist manufacturers in improving coating formulations to reduce the odor impact of coating products, we used headspace gas chromatography to determine the odor substances in water- and solvent-based coatings and analyzed the odor contribution of various volatile compounds using the odor activity value (OAV) method. Butyl acetate, ethylbenzene, and 1-methoxy-2-propyl acetate were the key odorants in solvent-based coatings while 1-butanol, ethylbenzene, and butyl acetate were the key odorants in water-based coatings.